The impact of health coaching on the prevention of gestational diabetes in overweight/obese pregnant women: a quasi-experimental study - Fateme Mohammadian; Mouloud Agajani Delavar; Fereshteh Behmanesh; Alireza Azizi; Sedighe Esmaeilzadeh (BMC, 2023)
Abstract Background Previous studies have demonstrated that excessive gestational weight gain (GWG) increases the risk of gestational diabetes mellitus (GDM). This study aimed to determine the effect of using health coaching on the prevention of GDM in overweight pregnant women. Methods In this quasi-experimental study, 64 eligible overweight women at 12-14 gestational weeks were randomly divided into 2 groups: the coaching group and the control group (usual care group). The intervention group received 8 weeks of the phone coaching program, which integrated GWG and physical activity to reduce the incidence of GDM. The Pregnancy Physical Activity Questionnaire (PPAQ) was used to assess physical activity during pregnancy. The occurrence of gestational diabetes was determined based on the 75-g 2-hour oral glucose tolerance test (OGTT) at 24-28 weeks of gestation. The primary outcome was the incidence of GDM, and the secondary outcomes included physical activity, GWG, and neonatal and maternal birth outcomes. Results The incidence of GDM in the control and intervention groups was 24.1% and 22.6%, respectively. The relative risk (RR) was 0.93 (95% CI, 0.37-2.34; P = 0.887). The post survey results indicated that GWG decreased more considerably in the coaching than in the control group between pre-trial (T0) and post-trial (T1), (MD; -2.49 with 95% CI, -4.38 to -0.60; P < 0.011). Moreover, the total GWG (between pre-pregnancy and birth) diminished more remarkably in the coaching than in the control group, (MD; -2.83 with 95% CI, -5.08 to -0.58; P < 0.014). However, the score of self-efficacy and concern about PPAQ Metabolic Equivalent of Task (METs) did not differ between the coaching and control groups. Conclusions The findings and implications of this research could significantly contribute to maternal health and gestational diabetes prevention. Additional support from a midwife coach resulted in better GWG. More studies are needed to assess the impact of health coaching as a component of usual care and its long-term effect on maternal and neonatal outcomes.